Urinary Tract Infection: Prescribing Pattern of Antibiotics at a Tertiary Care Hospital - L, Panayappan; Babu, Athira Suresh; Davis, Deena; Joseph, Neethu; Joshy, Neethu; K, Krishnakumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: The purpose of Drug Utilization Review is to ensure drugs are used appropriately, safely and effectively to improve patient health status. The use of drugs in appropriate, safe and effective manner would decrease the treatment cost for the patients. Urinary Tract infection is most common and can lead to secondary infections. So continuous analysis of prescribing pattern in urinary tract infection is a vital one. To find out the various risk factors of urinary tract infection. To study the Prescribing pattern and rational use of Antibiotics in UTI Patients in a tertiary care hospital. Methods: A prospective observational study was carried out in 100 patients in a tertiary care teaching hospital, by collecting patient data from the medical records of patients from General Medicine Department. Results: Analysis of prescribed drugs revealed that use of antibiotics like Ceftriaxone (35%) and Amikacin (22%) were significantly higher than other drugs prescribed such as Ciprofloxacin (16%), Nitrofurantoin (15%), Ofloxacin (5%), Cefixime (3%), Moxifloxacin (2%) and Clarithromycin (2%). Culture sensitivity test was done only in 30% of the total cases (100) for which empirical treatment had to be applied rather than specific antibiotic treatment. The most common isolated organisms were E.coli (60%),Proteus (20%), Klebsiella (13.33%) and Psedomonas (6.66%). Conclusion: Cephalosporins, Aminoglycosides and Quinolones were the most commonly prescribed antibiotics in this study. Present findings together with previous ones are suggestive the need of periodic monitoring of antibiotic sensitivity pattern of the bacterial isolates to provide effective treatment.